Acceptance of a potential major bleeding among patients with venous thromboembolism on long-term oral anticoagulation: the knowledge of the disease and therapy matters. Issue 193 (September 2020) - Konieczyńska, Małgorzata; Kupis, Robert W.; Bijak, Piotr; Malinowski, Krzysztof Piotr; Undas, Anetta
Abstract: Background: We investigated the bleeding tolerance and its determinants in anticoagulated patients with venous thromboembolism (VTE). Methods: In 153 outpatients after VTE which occurred in the absence of any identifiable risk factor (aged 52 ± 15.7 years, 54.9% male), anticoagulated for at least one month (for median 29, interquartile range [IQR] 11–72 months), the Bleeding Ratio was determined basing on the declared maximum number of major bleeds that patients can accept to prevent one similar recurrent VTE episode. The modified Jessa AF Knowledge Questionnaire (JAKQ-VTE) was used to assess the knowledge of VTE and anticoagulation. Results: The median of the Bleeding Ratio was 4 (IQR 2–6, minimum 1, maximum 10). Compared with patients with a high Bleeding Ratio (≥4 accepted bleedings, n = 91, 59.5%), those with a low Bleeding Ratio (0–3 accepted bleedings, n = 62, 40.5%) more frequently suffered from isolated deep vein thrombosis (DVT), recurrent VTE, and diabetes. The low Bleeding Ratio group had lower overall scoring in the JAKQ-VTE compared with the remainder (median, 60.4% vs 67.6%, p = 0.003). The independent predictors of a low Bleeding Ratio were: age (odds ratio [OR], 1.36; 95% confidence interval [CI] 1.06–1.75), history of isolated PE (OR, 0.24; 95% CI, 0.08–0.66), scores in the JAKQ-VTE (OR, 0.74; 95% CI, 0.57–0.95), and time since VTE diagnosis (OR, 1.05; 95% CI, 0.98–1.13). Conclusions: The current study suggests that the acceptance of potential major bleedings is associated not only with age and clinical factors, but also with the knowledge of VTE and anticoagulation, which highlights the need for educational efforts among patients requiring long-term anticoagulant therapy.